Positivity RT-PCR for COVID-19 and its determinants between compulsory notifications from healthcare professionals in a tertiary hospital (Research, Society and Development, 2022)
Introduction: The COVID-19 pandemic generated no impacts on a global scale, adding to recovery in the larger health system, lacking basic health services among basic services, lacking risk of basic education among health professionals. Objective: to analyze the epidemiological profile of cases of health professionals treated in a hospital and describe the determinants that influenced the positivity of RT-PCR. Methodology: cross-sectional retrospective research, approaching the calculated cases, based on suspected cases of COVID-19 health professionals treated at an university hospital in Triângulo Mineiro, Minas Gerais, Brazil. For all assessments, use SPSS software version 20.0. A significance of 5% was adopted. Results: data from notified health professionals were analyzed, with positivity for COVID-19 of 36.2% of the sample. Most of the population was from the nursing team (70.4%). The hospital sectors that have patients (58.8%) were positive in the professionals' RT-PCR (58,037). Professionals with a complete vaccination schedule showed a 43% reduction in chances (p = 0.044) of COVID-19 positivity. Conclusion: The greater positivity of RT-PCR may be related to professionals allocated in sectors with hospitalization, and in contrast, the protective factor against COVID-19 is the complete vaccination schedule.